Ambivalent binding between a radical-based pincer ligand and iron1. Issue 22 (14th June 2015) - Harriman, Katie L. M.; Leitch, Alicea A.; Stoian, Sebastian A.; Habib, Fatemah; Kneebone, Jared L.; Gorelsky, Serge I.; Korobkov, Ilia; Desgreniers, Serge; Neidig, Michael L.; Hill, Stephen; Murugesu, Muralee; Brusso, Jaclyn L.
<x xml:space="preserve">Abstract</x> An inherently redox active pincer-type ligand, 3, 5-bis(2-pyridyl)-1, 2, 4, 6-thiatriazinyl (Py2TTA˙), was employed to isolate Fe(Py2TTA)Cl2.